Development of Pop-Up Cultural Books Based on Cooperative Learning: Instilling Global Diversity Profiles in Elementary School Students - Wardana, Dewa Gede Krisna; Juwantara, Ridho Agung; Harjanto, Ambyah; Maximilian, Aksendro (Jurnal Inovasi Pendidikan Dasar, 2024)
This research aims to support the independent learning program, particularly in instilling the Pancasila student profile in elementary school students, which is examined through the process of developing a culture-based pop-up book using cooperative learning. This development research uses the ADDIE model and data collection tools in the form of questionnaires, interviews, and tests. This research is analyzed and explained with numerical and descriptive data. Based on the research results, the media validation obtained is 97.5% with the criteria "Very Feasible." The results of the material validation are 87.2% with the criteria "Very Feasible." The small group test yielded an average of 100% with the criterion "Very Interesting." Field trials obtained an average score of 99% with the criterion "Very Interesting." The effectiveness test yielded an average of 87% with a "Very High" effectiveness category. This research shows that the development of pop-up books based on cooperative learning is highly needed and feasible to use, especially to support students' understanding of regional cultural introduction and the absorption of a global diversity profile.